Construction of a compound microbial agent for biocontrol against Fusarium wilt of banana - Du, Chanjuan; Yang, Di; Ye, Yunfeng; Pan, Lianfu; Zhang, Jin; Jiang, Shangbo; Fu, Gang (Frontiers in Microbiology, 2022)
Banana wilt caused by Fusarium oxysporum f. sp. cubense has devastated a large number of banana plantations worldwide. Biological control is a possible method to conquer this disease. However, the control effect was often low and unstable while a single biocontrol strain had been applied in the field. Therefore, this study aimed to construct an effective compound microbial agent to control Fusarium wilt of banana (FWB) in the field. In addition to it, the compounding strategy of combining single strains for improving the control effect was investigated. Based on the compatibility test, five representative biocontrol strains were selected for the combination of all possible permutations. The pot experiment indicated that every biocontrol strain and their 26 combinations could control FWB to varying degrees. The control effect of combinations on FWB was higher than that of a single strain. In terms of the number of combinatorial biocontrol strains, the control effect of the four-strain combinations was the highest. According to the taxonomic differences of the five biocontrol strains, 26 biocontrol strain combinations could be divided into four groups. Among the strains in the combination, the larger the taxonomic differences the more easily it was to obtain a higher control effect. To obtain stable and efficient combinations, eight combinations were selected out and evaluated for their effectiveness in controlling FWB in different type soil. Compared with the other seven combinations, the four-strain combination T28 (Pt05 + Bc11 + Ba62 + gz-2) got the highest and stablest control effect in the four types of soil in greenhouse. And then the control effect of combination T28 was evaluated in field conditions, compared with commercially agents Bacillus subtilis, Trichoderma harzianum, and carbendazim. After four consecutive applications in the field, the control effect of T28 against FWB was the highest, reaching 57.14%. The results showed that combination T28 had a good application prospect, and the finding provided a reference for the construction of compound microbial agents.